2013
DOI: 10.1161/strokeaha.111.000361
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Movement Therapy Overcomes the Intrinsic Axonal Growth–Inhibitory Signals in Stroke Rats

Abstract: Forty-two male Wistar rats (200-250 g) were randomly assigned as sham-operated rats (SHAM; n=12), rats subjected to cerebral ischemia (ISC; n=15), and rats with cerebral ischemia that were later treated with CIMT (ISC+CIMT; n=15). All rats were housed under controlled temperature in a 12-hour light/dark cycle with easy access to food and water and assigned to groups with a minimum of 4 animals per enclosure. Protocols and procedures were approved by the Institutional Animal Care and Use Committee of China Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 42 publications
(67 reference statements)
5
42
0
Order By: Relevance
“…The reason for these contradictory results might lie in the different locations of the lesions (cortical vs subcortical). Use-dependent exaggeration of neuronal injury has been reported in cortical injury models [16,[25][26][27]. In addition, neuronal cell bodies seemed to be more vulnerable to excitotoxicity in contrast to their axons [10,12,28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reason for these contradictory results might lie in the different locations of the lesions (cortical vs subcortical). Use-dependent exaggeration of neuronal injury has been reported in cortical injury models [16,[25][26][27]. In addition, neuronal cell bodies seemed to be more vulnerable to excitotoxicity in contrast to their axons [10,12,28].…”
Section: Discussionmentioning
confidence: 98%
“…However, we must also consider the possibility that early CIMT can down-regulate inhibitory factors such as the Nogo-A receptor or RhoA/Rho-associated kinase [27]. neurons of the ipsi-lesional motor cortex, as has been reported in cases of denervated spinal cord [8].…”
Section: Page 16 Of 35mentioning
confidence: 99%
“…Previous reports demonstrated that early application of forced impaired forelimb use facilitated the side switching of corticospinal fibers originating from the contralesional hemisphere in the cervical cord after transection of the unilateral pyramidal tract (Maier et al, 2008). These intraspinal recrossed sprouting fibers from the intact descending tract can also be an important substrate for recovery after unilateral motor cortex infarction (Zhao et al, 2013;Wahl et al, 2014). Conversely, the present data revealed that the ipsilesional affected motor cortex and its axons descending to the red nucleus were involved in FLU-induced reorganization and recovery after ICH, which perhaps depends on the extent of damage to the corticospinal system.…”
Section: Flu Enhances Plasticity In the Ipsilesional Motor Cortex Aftmentioning
confidence: 99%
“…Brain imaging studies of stroke patients indicated that CIMT induced expansion of the forelimb representative area in the sensorimotor cortex after stroke (Liepert et al, 1998;Sawaki et al, 2008). Moreover, studies using rodent models reported forced impaired limb use-induced anatomical changes of the CNS such as sprouting from the ipsilateral corticospinal tract (CST) to the denervated cervical cord (Maier et al, 2008;Zhao et al, 2013). However, it has been difficult to demonstrate the causal linkage between reorganization of the circuit and behavioral recovery.…”
Section: Introductionmentioning
confidence: 99%
“…When use of the left, stroke-affected paw was obligatory for a task (e.g., on the rotating rod) (Fig. 1C-E), performance gradually recovered, suggesting a functional recovery of the affected forepaw (Bury and Jones, 2002;Nakagawa et al, 2013;Zhao et al, 2013).…”
Section: Motor Behavior Partially Recovers After Unilateral Motor Cormentioning
confidence: 99%